Amperometric Biosensor with Interdigitated Au Electrode for Rapid Detection of Enterococcus faecalis in Water Samples - SESAL, NÜZHET CENK (AMER SCIENTIFIC PUBLISHERS, 2013)
Enterococcus faecalis (E. faecalis) in water samples were detected using an amperometric biosensor based on interdigitated arrays of Au electrodes (IAE). Anti-E. faecalis antibodies were immobilized on IA electrodes via self-assembled monolayers-based amine coupling chemistry. The specific binding of target bacteria on the surface immobilized antibodies was verified by an increase of the sensor's conductivity. The E. faecalis detection measurements revealed that the specific adsorption of E. faecalis onto the immobilized anti-E. faecalis antibody gave rise to a clear increase in the value of sensor current. Current changes induced by the binding of E. faecalis to the anti-E. faecalis antibodies on the IAE's surface enabled target bacteria to be detected in a highly sensitive way-a detection limit of less than 1.0 x 10(3) CFU/ml and a response time of 200 s. The effect of the temperature and pH on the E. faecalis sensing properties of the sensor were also investigated. From the temperature dependency of response curves, it was observed that the sensitivity of the sensor decreases with increasing temperature.
Keywords: Amperometric Biosensor; Enterococcus faecalis; Response Time; Sensitivity; IMMUNOSENSOR